\(\frac{x+5}{-7}=\frac{5}{30-y}=\frac{49}{49}=1\)
\(\Rightarrow\hept{\begin{cases}\frac{x+5}{-7}=1\\\frac{5}{30-y}=1\end{cases}\Leftrightarrow\hept{\begin{cases}x+5=-7\\5=30-y\end{cases}\Leftrightarrow}\hept{\begin{cases}x=-7-5\\y=30-5\end{cases}\Leftrightarrow}\hept{\begin{cases}x=-12\\y=25\end{cases}}}\)
\(\frac{x+5}{-7}=\frac{5}{30-y}=\frac{7^2}{49}\)
\(\frac{x+5}{-7}=\frac{5}{30-y}=\frac{49}{49}=1\)
\(\Rightarrow\frac{x+5}{-7}=\frac{-7}{-7}\) và \(\frac{5}{30-y}=\frac{5}{5}\)
\(\Rightarrow x=-12;y=25\)
\(\frac{x+5}{-7}=\frac{5}{30-y}=\frac{7^2}{49}=\frac{49}{49}=1\)
\(\Leftrightarrow\hept{\begin{cases}\frac{x+5}{-7}=1\\\frac{5}{30-y}=1\end{cases}\Leftrightarrow\hept{\begin{cases}x+5=-7\\30-y=5\end{cases}\Leftrightarrow}\hept{\begin{cases}x=-7-5\\y=30-5\end{cases}\Leftrightarrow}\hept{\begin{cases}x=-12\\y=25\end{cases}}}\)